The book as artefact, text and border - Hansen, Anne Mette (Variants, 2005)
The Book as Artefact Books do not just contain texts: books themselves are cultural artefacts, which convey many meanings in their own right, meanings which interact with the texts they contain. Awareness of the many significances of books as cultural and textual objects reshapes the traditional disciplines of textual theory, analytic bibliography, codicology and palaeography, while the advent of electronic books, and digital methods for representing print books, is introducing a new dimension to our understanding. Seven essays in this volume, ranging over medieval Portuguese and Swedish manus.